2010
DOI: 10.1039/c0ay00235f
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the derivatization and quantification of dialkyl phosphate esters in petroleum samples

Abstract: Dialkyl phosphate esters are used as gellants in some oil well fracturing processes for conventional oil production. Residual amounts of these compounds that remain in the well represent a source of potential contamination of the crude oil produced from the well. This contamination results in fouling of refinery equipment. Current methodologies for the analysis of alkyl phosphates have a relatively poor detection limit (0.5 AE 1.0 mg mL À1 ) and provide no speciation information: only a total phosphorus concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…8,15−23 For the speciation of di-and trialkyl phosphates in petroleum samples, we first introduced a method based on trimethylsilylation derivatization followed by GC × GC separation using a flame ionization detector (FID). 24 Although this analytical approach yielded quantification limits and a level of precision that exceeded the capabilities of the currently accepted ICP− OES methodology, our research demonstrated the necessity for selective detection in this application. We achieved selective detection through the use of time-of-flight mass spectrometry (TOFMS), 25 and overall, this technique was capable of both speciation and quantification of alkyl phosphates in petroleum samples with better precision and lower limits of quantification when compared to ICP−OES.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…8,15−23 For the speciation of di-and trialkyl phosphates in petroleum samples, we first introduced a method based on trimethylsilylation derivatization followed by GC × GC separation using a flame ionization detector (FID). 24 Although this analytical approach yielded quantification limits and a level of precision that exceeded the capabilities of the currently accepted ICP− OES methodology, our research demonstrated the necessity for selective detection in this application. We achieved selective detection through the use of time-of-flight mass spectrometry (TOFMS), 25 and overall, this technique was capable of both speciation and quantification of alkyl phosphates in petroleum samples with better precision and lower limits of quantification when compared to ICP−OES.…”
Section: Introductionmentioning
confidence: 78%
“…For this situation, a NPD is a better choice, although it requires a Deans switch for detector selection to divert excess silylation reagents at the start of a chromatogram to a FID . This protects the NPD bead, which would be rapidly (<10 injections) passivated with an inert layer of SiO 2 when exposed to excess silylation reagents. , Using the Deans switch after the secondary column in GC × GC for detector selection extended the lifetime of the NPD bead from approximately 5 injections to over 1000, performed over the course of 15 months . The resulting GC × GC–FID/NPD system offered an approach that was capable of both quantifying and speciating individual alkyl phosphate compounds in industrial petroleum samples.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations